INOVASI DAN PENERIMAAN TEKNOLOGI: TINJAUAN DARI PERSPEKTIF TEN TYPES OF INNOVATION, TAM, DAN UTAUT - Agus Widayoko; Selvy Herawati; Nasirin (SMA Trensains Muhammadiyah Sragen, 2026)
Innovation and technology acceptance are two fundamental aspects that determine the success of organizations in the digital era. Innovation is not only limited to the creation of new products, but also encompasses how organizations manage business models, build customer experiences, and utilize networks and technology. Keeley (2013) in Ten Types of Innovation emphasizes that innovation can appear in various forms—from internal configurations and product offerings to interactions with customers. However, no matter how good an innovation is, its success is largely determined by the extent to which the technology or system is accepted by users. Davis (1989) with the Technology Acceptance Model (TAM) provides a basic framework for understanding technology acceptance through two main factors: perceived usefulness and perceived ease of use. This model is widely applied in education, healthcare, e-commerce, e-government, and industry. Meanwhile, Venkatesh et al. (2003) expanded this perspective through the Unified Theory of Acceptance and Use of Technology (UTAUT) by adding social factors and supporting conditions, and considering the influence of moderators such as age, gender, experience, and level of voluntary use. This article compares these three frameworks in accessible language, highlighting their relevance in supporting digital transformation across various sectors. By combining the perspectives of innovation and technology acceptance, this paper emphasizes that the success of an innovation depends not only on creativity in creating a new product or service, but also on the ease, benefits, and supportive environment that encourages its adoption. These findings are relevant for researchers, practitioners, and policymakers seeking to design sustainable innovations that are truly accepted and utilized by the wider community.